Sport Photography on Social Media as Digital Discourse and Visual Semiotics: A Meta-Analysis - Monica Maudi Sundara; Miftakhul Jannah; Damajanti Kusuma Dewi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The increasing use of social media has transformed sport photography from a form of visual documentation into a complex medium of digital discourse and visual semiotics. This study examines sport photography as a multimodal communicative practice while simultaneously synthesizing empirical evidence through a meta-analytic approach. The urgency of this research lies in the fragmentation of previous studies, which tend to examine engagement, branding, or gender representation separately without providing an integrative and quantitative synthesis. This study employs a systematic literature review and meta-analysis following PRISMA 2020 guidelines, analyzing 30 peer-reviewed studies published between 2022 and 2026. Of these, only studies with sufficient quantitative data were included in the meta-analysis, while the remaining studies supported qualitative synthesis. The findings reveal a moderate overall effect size (g = 0.44), indicating that sport photography has a significant yet context-dependent influence on audience engagement and perception. The heterogeneity value (I² = 64.3%) demonstrates substantial variation across platforms, cultural contexts, and methodological approaches. These results indicate that sport photography functions not only as visual representation but also as a dynamic semiotic resource that constructs meaning, identity, and ideological discourse in digital environments. In conclusion, this study contributes by integrating digital discourse, visual semiotics, and meta-analysis to provide a comprehensive understanding of sport photography in contemporary media.